Sorption of trivalent chromium from tannery waste by moss - Low, K.S.; Lee, C.K.; Tan, S.G. (Selper, 1997)
The sorption of Cr(III) from synthetic solution and tannery waste using moss, Calymperes delessertii Besch, was conducted under laboratory conditions to assess its potential in removing Cr(III). Parameters investigated include pH, contact time, initial concentration and sorbent dosage. Results obtained from isotherm studies show that the sorption of Cr(III) by moss followed the Langmuir isotherm and the maximum sorption capacities were 15.4 and 13.7 mg g−1 for synthetic solution and tannery waste respectively.